Metabarcoding Reveals Seasonal and Temperature-Dependent Succession of Zooplankton Communities in the Red Sea - Casas, Laura; Pearman, John K.; Irigoien, Xabier (Frontiers in Marine Science, 2017)
Very little is known about the composition and the annual cycle of zooplankton assemblages in the Red Sea, a confined water body characterized by a high biodiversity and endemism but at the same time one of the most understudied areas in the world in terms of marine biodiversity. This high diversity together with the lack of references for several of the groups poses a problem in obtaining basic information on zooplankton seasonal patterns. In the present work, we used high throughput sequencing to examine the temporal and spatial distribution of the zooplankton assemblages inhabiting the epipelagic zone in the central Red Sea. We provide baseline information of the seasonal patterns of the zooplankton community over one year. We show that the seasonal fluctuation of zooplankton communities living in the upper 100 meters of the water column is driven mainly by the annual changes in seawater temperature. Metabarcoding of zooplankton assemblages revealed 630 metazoan OTUs (97 % similarity) in five phyla, highlighting the richness of the Red Sea community. During colder months, communities were characterized by lower richness and higher biomass than communities found during the hot season. Throughout the year the zooplankton communities were dominated by the class Maxillopoda, mainly represented by copepods and class Hydrozoa. The rise in the water temperature favors the appearance of classes Malacostraca, Cephalopoda, Gastropoda and Saggitoidea.